Adsorptive removal of fluoride from water using hydroxyapatite synthesized from marine shell waste - Shantanu Singh; Gokulakrishnan Murugesan; Ramesh Vinayagam; Thivaharan Varadavenkatesan; Raja Selvaraj (Scientific Reports)
Abstract Fluoride contamination in groundwater threatens human health and ecological systems, necessitating cost-effective and efficient remediation strategies. This study synthesized hydroxyapatite (MRS-HAp) from Marcia recens shells through chemical precipitation to serve as a potential adsorbent for the removal of fluoride. The prepared MRS-HAp exhibited a specific surface area of 100.42 m2/g. FESEM analysis revealed an irregular, closely packed structure with a mean diameter of 28.89 nm. EDS determined a Ca/P molar ratio of 1.6, while XRD analysis confirmed a hexagonal crystalline lattice with a crystallite diameter of 32.18 nm. XPS identified a fluoride peak at 684.58 eV, confirming adsorption. The adsorption dataset obeyed pseudo-second-order kinetics and Langmuir isotherm, pointing to chemisorption and monolayer coverage, with a maximum adsorption capacity of 19.19 mg/g. Spiked water experiments demonstrated robust fluoride removal efficiencies across diverse real-world water matrices. MRS-HAp showed reasonable regeneration potential for fluoride removal, retaining significant adsorption capacity over four cycles. These results position MRS-HAp as a cost-effective and sustainable adsorbent for fluoride removal in water treatment applications.